Peranan Sistem Penjualan Dalam Kaitannya Dengan Kolektibilitas Piutang - Marlina, Tri; Danial, M; Susmiatik, Susmiatik (Jurnal Ilmiah Akuntansi Kesatuan, 2015)
A company is established to seek maximum profit and to maintain the viability of their bussines. Bussines continuity can be achieved if the goods or services offered can be accepted by consumers. It is therefore important for companies to learn sales system, Sales is one important aspect of a company. One way that is used to increase sales is by using credit sales. Which of the credit sales will cause accounts to be controlled and should be evaluated for collectibity. On the basic of the above conditions is necessary to determine the role of sales system in relation to the collectability of receivables. The study aims to determine the adequacy of the implementation of the sales system, to determine the collectability of accounts receivable company, and to detenninethe role of sales system in relation to the collectability of receivables. The result showed that the system of sale of the company is enough with marked pencentage of bad debts is quite low relative. Keywords: Sales Systems, Collectability of Receivable